Identification of failure mechanisms by internal rupture of geocell retaining walls through centrifuge modelling (2012)
Geocells earth retaining structures are in expansion at the present times worldwide. However, there is still the need for a clear design procedure that must be reliable and in accordance with the real retaining structure behaviour. The objective of this work is to perform a geotechnical centrifuge study at 20g, by means of the elaboration of several centrifuge model tests on Geocells gravity retaining walls with the purpose to investigate and examine their structural capacity and failure mechanism under a critical loading, including incremental surcharge and water flow.